HOTS-Based Booklet Media Development in Learning to Analyze The Mandate of Poetry - Badri'ah, Badri'ah; Sulistyorini, Dwi; Zuhairi, Aminudin (research, training and philanthropy institution Natural Aceh, 2024)
Education plays a crucial role in developing human potential and higher-order thinking skills. Today, educators are required to be more creative, productive, and competitive. Learning media such as HOTS-based booklets (Higher Order Thinking Skills) are one of the solutions to increase the effectiveness of learning. The booklet, presented briefly and clearly, equipped with illustrative images, and easy to carry, can help students understand the material better. This study aims to develop, analyze the validity, and test the effectiveness of HOTS-based booklet media in learning to analyze poetry mandates. This research includes research and development referring to the modified 4-D model of S. Thiagarajan, et al. The instruments used in the collection of research data consist of validity testing instruments in the form of validation sheets of experts and interview instruments used to obtain validity data in the field. . The results of the study show that: (1) The validity level of the learning media that has been revised by 3 validators is in the valid category with an average score of all aspects of 3.6. (2) The level of effectiveness of the development of HOTS-based booklet media for grade IV students of SDN 3 Joho Pace Nganjuk obtained an average score of 3.6. (3) In the validity test in the field, the average response was positive to the use of booklet media. The use of booklets as a learning medium can improve student learning outcomes and help teachers deliver material better.